2015
DOI: 10.1021/acs.inorgchem.5b02132
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Salt Flux Crystal Growth of New Lanthanide Molybdenum Oxides, Ln5Mo2O12 Ln = Eu, Tb, Dy, Ho, and Er: Magnetic Coupling within Mixed Valent Mo(IV/V) Rutile-Like Chains

Abstract: Five new lanthanide molybdenum oxides containing mixed valent Mo(IV/V) rutile-like chains, Ln5Mo2O12 Ln = Eu, Tb, Dy, Ho, and Er, were prepared utilizing a high-temperature molten salt flux synthesis involving an in situ reduction utilizing metallic reducing agents. All five compounds were structurally characterized by single-crystal and powder X-ray diffraction methods and were found to crystallize in the monoclinic space group C2/m. The molybdates all contain rare infinite chains consisting of MoO2O4/2 edge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…It is suggested that these short distances are the result of metal–metal bonds, leaving one unpaired electron per B 2 O 10 dimer. [ 37–39,45 ] For example, in Y 5 Re 2 O 12 , the average Re oxidation is +4.5, which results in 2.5 electrons per Re atom, or 5 electrons per rhenium dimer, and 4 of these electrons can be assigned to form a Re=Re double bond, leaving one unpaired electron per rhenium dimer to create an S = 1/2 local moment per formula unit. Similarly, the Ln 5 Mo 2 O 12 series in which Mo is in the formal +4.5 oxidation state contains three electrons per molybdenum dimer, generating one bond and one unpaired electron per formula unit.…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that these short distances are the result of metal–metal bonds, leaving one unpaired electron per B 2 O 10 dimer. [ 37–39,45 ] For example, in Y 5 Re 2 O 12 , the average Re oxidation is +4.5, which results in 2.5 electrons per Re atom, or 5 electrons per rhenium dimer, and 4 of these electrons can be assigned to form a Re=Re double bond, leaving one unpaired electron per rhenium dimer to create an S = 1/2 local moment per formula unit. Similarly, the Ln 5 Mo 2 O 12 series in which Mo is in the formal +4.5 oxidation state contains three electrons per molybdenum dimer, generating one bond and one unpaired electron per formula unit.…”
Section: Resultsmentioning
confidence: 99%
“…For many years now, we have demonstrated that alkali halide fluxes can serve as excellent media in which a rather extensive list of elemental or binary reagents can be dissolved and from which single crystals can be grown. Furthermore, such flux growth reactions result in a good yield of crystals that can be readily isolated by dissolving the flux and can be used for property measurements. In addition to the exploration of new oxides, we are now pursuing the use of alkali halide fluxes for growing single crystals of new complex metal sulfides with interesting physical properties. So far, we have successfully synthesized a family of uranium-containing thiophosphates, featuring complex topologies, from alkali iodide melts and reported on their magnetic and optical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, the monoclinic lattice parameters of this compound were in general agreement with those described earlier for a series of compounds reported to have the composition Ln 4 Mo 2 O 10 , where the investigated trivalent cations in the powder syntheses included the readily accessible lanthanoids from La–Lu as well as Y. From these prior investigations, it can tentatively be concluded that 1D chains of Mo 2 O 10 dimers should exist for all Ln 5 Mo 2 O 12 compounds and that there are as-yet unresolved structural complexities in this family of materials that were not elucidated in single crystal diffraction studies. Additionally, some prior structural refinements of Ln 5 M 2 O 12 ( Ln = Y, Pr, Nd, and Sm–Tb; M = Re and Ru) single crystal diffraction data in the C 2/ m space group make use of minority sites to model extra density observed in Fourier difference maps with refined minority site occupancies of 2.3% in Y 5 Re 2 O 12 and 4.4% in Ln 5 Ru 2 O 12 . , In other single crystal studies of Ln 5 Mo 2 O 12 phases within in the C 2/ m space group, minority sites were not used in the final structural model. , …”
Section: Introductionmentioning
confidence: 99%